MELTA NATIONAL CONVENTION ON LITERATURE 16TH APRIL 2005 KEYNOTE ADDRESS - Hajah Noor Rezan (The English Teacher, 2005)
It is my pleasure this morning to speak before such an eclectic and informed group of people – representatives from the various departments of the MOE, teachers, the valuable practitioners from all levels of the education structure, members of the press, publishers, relevant NGOs, teacher trainers and university personnel. I would also like to thank MELTA for inviting me to deliver the keynote address at this one-day convention, The MELTA National Convention on Teaching Literature. I also congratulate MELTA for investing time and energy to bring together language practitioners, researchers, policy-makers and others, to discuss a matter of great and grave concern to all of us present here today – The Teaching of Literature in an ESL context.